2018
DOI: 10.1186/s12199-017-0691-y
|View full text |Cite
|
Sign up to set email alerts
|

Sharp injuries: a cross-sectional study among health care workers in a provincial teaching hospital in China

Abstract: BackgroundThe objectives of this study are to investigate the incidence and reporting behavior of sharp injuries among healthcare workers (HCWs) and identify the risk factors associated with these injuries.MethodsA cross-sectional survey was conducted in February 2017 in a provincial teaching hospital in China. Data were collected from 901 HCWs using a self-administered questionnaire which included demographic information, experience, and reporting behavior of sharp injuries. Stepwise logistical regression was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
6
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 29 publications
6
40
6
2
Order By: Relevance
“…In the current study, recapping of needle was the most common activity leading to NSIs (56.3%) followed by while doing 17,18,21,22 the procedure (54.2%)-this was consistent with other studies. In the current study, less than half of the study subjects (43.2%) had comprehensive knowledge about universal precaution guidelines in comparison to better knowledge reported by studies from Tamil Nadu 16,24 and China (73.2% & 75.1% respectively). The present study showed majority of the study subjects know HIV/AIDS, Hepatitis B and Hepatitis C (93.4%, 94.8% and 82.7% respectively) are transmitted by NSIs which is consistent with studies from Assam & 23,24 Tamil Nadu.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…In the current study, recapping of needle was the most common activity leading to NSIs (56.3%) followed by while doing 17,18,21,22 the procedure (54.2%)-this was consistent with other studies. In the current study, less than half of the study subjects (43.2%) had comprehensive knowledge about universal precaution guidelines in comparison to better knowledge reported by studies from Tamil Nadu 16,24 and China (73.2% & 75.1% respectively). The present study showed majority of the study subjects know HIV/AIDS, Hepatitis B and Hepatitis C (93.4%, 94.8% and 82.7% respectively) are transmitted by NSIs which is consistent with studies from Assam & 23,24 Tamil Nadu.…”
Section: Discussioncontrasting
confidence: 77%
“…34% --76%) among the HCWs. Only one quarter of the health personnel were trained in last one year on NSIs in this study, while another study from China reported 'often training' given among 43.1% 16 of HCWs.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…It was found that (54.54%) of needle stick injuries were not reported. Among injury exposures, [8] in a study of Cui et al [21] sharp injuries among the studied subjects were commonly underreported. Also, the possible reasons for needle stick injuries from Sharma's [22] study; the greater part of injuries (48%) occurred after needle use but before disposal and only 6.8% during disposal of the needle when recapping needle was observed to be the most frequent procedure.…”
Section: Considering Causes For Not Reporting Needle Stick In-mentioning
confidence: 90%
“…Dari Pada studi-studi sebelumnya, dilaporkan bahwa dokter dan perawat paling sering terpajan cairan berisiko. [15][16][17] Hal ini juga terlihat pada penelitian ini, yaitu profesi dokter sebagai mayoritas pembuat laporan pajanan (49,5%). Hasil ini tidak beda jauh dengan penelitian oleh Nouetchognou, dkk.…”
Section: Pendahuluanunclassified